Identification of a Technique Optimized for the Isolation of Spermatogonial Stem Cells from Mouse Testes - Na Rae Han; Hye Jin Park; Hyun Lee; Jung Im Yun; Kimyung Choi; Eunsong Lee; Seung Tae Lee (The Korean Society of Animal Reproduction and Biotechnology, 2018)
To date, there are no protocols optimized to the effective separation of spermatogonial stem cells (SSCs) from testicular cells derived from mouse testes, thus hindering studies based on mouse SSCs. In this study, we aimed to determine the most efficient purification method for the isolation of SSCs from mouse testes among previously described techniques. Isolation of SSCs from testicular cells derived from mouse testes was conducted using four different techniques: differential plating (DP), magnetic-activated cell sorting (MACS) post-DP, MACS, and positive and negative selection double MACS. DP was performed for 1, 2, 4, 8, or 16 h, and MACS was performed using EpCAM (MACSEpCAM), Thy1 (MACSThy1), or GFRα1 (MACSGFRα1) antibodies. The purification efficiency of each method was analyzed by measuring the percentage of cells that stained positively for alkaline phosphatase. DP for 8 h, MACSThy1 post-DP for 8 h, MACSGFRα1, positive selection double MACSGFRα1/EpCAM, and negative selection double MACSGFRα1/α-SMA were identified as the optimal protocols for isolation of SSCs from mouse testicular cells. Comparison of the purification efficiencies of the optimized isolation protocols showed that, numerically, the highest purification efficiency was obtained using MACSGFRα1. Overall, our results indicate that MACSGFRα1 is an appropriate purification technique for the isolation of SSCs from mouse testicular cells.